MMIC low noise amplifier for 5.8 GHZ ISM band applications - Cheong, Ban Chuan. (2008)
In this dissertation, the design and optimisation of a monolithic two-stage low noise amplifier specifically for 5.8 GHz ISM band are presented. The design is based on a two-stage low noise amplifier having a current sharing technique with a cascode DC configuration. However, from an RF standpoint of view, each stage is connected in a cascade configuration. It was shown through simulation that the smaller unit gate width (UGW) device yields better NF performance and actual measurement of the circuit gives the same conclusion.